A Comprehensive Review of the Ketamine Mechanism and Its Pleiotropic Effects - Taqwa B. Thanoon; Zeina Althanoon (University of Mosul, 2024)
Objective: In the world of anesthetics, ketamine is unique. Over thirty years ago, the substance was first used in therapeutic practice to act as a "mono-anesthetic," causing analgesia, forgetfulness, loss of consciousness, and immobility. ketamine is frequently found in equal amounts as the enantiomers S(-) and R(+)-ketamine in a racemic mixture. From a pharmacological perspective, glutamate, the primary excitatory neurotransmitter in the brain, is the primary target of ketamine. It is a non-competitive antagonist Working at one of the three glutamate receptors, the N-methyl d-aspartate (NMDA) receptor. Despite of its side effects, ketamine has shown to be an effective treatment due to its short half-life and lack of clinically significant respiratory depression. Aim: the review sought to highlight the important neurobehavioral activity of ketamine in the light of its agonist of mu, delta, and kappa opioid receptors. Methods: That included online published materials from Google Scholar, PubMed, Medline, and many other websites to gather as much as possible of information together. Conclusions:  Ketamine, is  a potent anesthetic and psychotropic drug. Beyond its antidepressant properties, ketamine has also been investigated for its potential in treating chronic pain, post-traumatic stress disorder (PTSD), and substance use disorders.